1989
DOI: 10.1152/ajpheart.1989.257.5.h1354
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of microvessel wall charge by plasma glycoprotein orosomucoid

Abstract: Haraldsson and Rippe suggested that the circulating glycoprotein orosomucoid (alpha 1-acid glycoprotein) contributes to the net charge on microvessel walls (Acta Physiol. Scand. 129: 127-135, 1987). We tested their hypothesis in individually perfused microvessels of frog mesentery by measuring solute permeability coefficients of two globular proteins (alpha-lactalbumin and ribonuclease) having approximately the same size (Stokes radius, 2 nm) but different charge (-11 and +3, respectively). In vessels perfused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 0 publications
1
55
0
1
Order By: Relevance
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
See 2 more Smart Citations
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
“…Thus, it restricts the extravasation of anionic macromolecules, as has been demonstrated in cultured endothelial cell monolayer (Sahagun et al, 1990) and various normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989). Adamson et al (1988) have demonstrated that the microvascular permeability to α-lactalbumin (M r = 14 176, net charge -10) is approximately 50% of that to ribonuclease (M r = 13 683, net charge +4), suggesting that the microvascular permeability to the positively charged molecules is higher than the permeability to the negative ones.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…29,35 Orosomucoid is also bound to the surface of cultured bovine pulmonary microvascular endothelial cells. 36 It has been found that orosomucoid modulates the transport of charged solutes across the wall of peripheral and cerebral microvessels in vivo by decreasing the transport of negatively charged molecules but increasing that of positively charged ones, 13,23,46 suggesting that orosomucoid plays an essential role in maintaining the permeability property of endothelium by adding negative charge to the SGL. 13,23,38 The second objective of the present study is thus to investigate whether orosomucoid modulates the bEnd3 monolayer permeability in a similar way as it does for the intact endothelium of the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, injection of exogenous ORM protects mice from TNF␣-induced lethality (18). Additionally, it has been proposed that ORM changes the polyanionic charge selectivity of capillary walls, and thereby plays the role of a barrier for capillary permeability (19,20). Another interesting feature of ORM is associated with its structure.…”
mentioning
confidence: 90%